2016
DOI: 10.3171/2015.10.peds15318
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of hospital discharge on postoperative Day 1 following uncomplicated tethered spinal cord release

Abstract: OBJECTIVE Postoperative management following the release of simple spinal cord–tethering lesions is highly variable. As a quality improvement initiative, the authors aimed to determine whether an institutional protocol of discharging patients on postoperative day (POD) 1 was associated with a higher rate of postoperative CSF leaks than the prior protocol of discharge on POD 2. METHODS This was a single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…This was attributed to the fact that postoperative pain was less with the ILA technique. In our study, the rates of postoperative complications requiring reoperation were 1.8% and 2.0% in the ILA and LOA groups, respectively, which were lower than those in previous reports [2,5,6,10,14,20,21,25,31].…”
Section: Comparison With Literature Reports On Complicationscontrasting
confidence: 82%
See 1 more Smart Citation
“…This was attributed to the fact that postoperative pain was less with the ILA technique. In our study, the rates of postoperative complications requiring reoperation were 1.8% and 2.0% in the ILA and LOA groups, respectively, which were lower than those in previous reports [2,5,6,10,14,20,21,25,31].…”
Section: Comparison With Literature Reports On Complicationscontrasting
confidence: 82%
“…Bhimani et al [2] reported a complication rate of 8.1% with a single laminotomy. Complication rates in other studies were 1.8-9.2% [5,10,14,20,21,31].…”
Section: Comparison With Literature Reports On Complicationsmentioning
confidence: 74%
“…Ample studies have examined the optimal duration that patients should remain flat in the context of simple tethered cord, but no quality prospective studies have analyzed this factor for complex tethered cords. 23,24,28,29 Consensus was reached for a minimum duration of 24 hours of flat positioning postoperatively (94.14% agree or strongly agree). A significant proportion of the group kept patients flat for 48 hours or more, but not at a level sufficient for consensus.…”
Section: Postoperative Best Practice Statementsmentioning
confidence: 99%